2011
DOI: 10.3347/kjp.2011.49.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofClonorchis sinensisMetacercariae in Freshwater Fish from Three Latitudinal Regions of the Korean Peninsula

Abstract: A large-scale survey was conducted to investigate the infection status of fresh water fishes with Clonorchis sinensis metacercariae (CsMc) in 3 wide regions, which were tentatively divided by latitudinal levels of the Korean peninsula. A total of 4,071 freshwater fishes were collected from 3 regions, i.e., northern (Gangwon-do: 1,543 fish), middle (Chungcheongbuk-do and Gyeongsangbuk-do: 1,167 fish), and southern areas (Jeollanam-do, Ulsan-si, and Gyeongsangnam-do: 1,361 fish). Each fish was examined by the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 28 publications
3
51
0
Order By: Relevance
“…However, Cs Mc were not detected in fish from the water systems of Han-gang in Gangwon-do [14,15]. In fish from Geum-gang, the prevalence and density of Cs Mc were also revealed in low levels [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, Cs Mc were not detected in fish from the water systems of Han-gang in Gangwon-do [14,15]. In fish from Geum-gang, the prevalence and density of Cs Mc were also revealed in low levels [14].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 14 ] reported that all fishes from upper regions of Cheongju-si, Chungcheongbuk-do were negative for C. sinensis metacercariae. However, Cho et al [ 15 ] detected C. sinensis metacercariae in 2 fish species, Pungtungia herzi and Squalidus japonicus coreanus , only from Hantangang in Cheorwon-gun, among 9 localities surveyed in Gangwon-do. Cho et al [ 22 ] also found them in 4 fish species, i.e., P. herzi , S. japonicus coreanus , Acheilognathus rhombeus , and Ladislabia taczanowskii , from Hantangang in Cheorwon-gun.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated the infection status of 9 DTM, i.e., C. sinensis , Metagonimus spp., C. armatus , Echinostoma spp., Diplostomum sp., Stephanoprora sp., M. orientalis , M. taiwanensis , and C. complanatum , and did not detect 5 species, i.e., Metacercaria hasegawai , E. oviformis , P. major , C. orientalis , and H. nipponicum , among the list of DTM described previously. The present study is meaningful as the first trial on the investigation of DTM infections in fishes from the northern regions of the Korean peninsula, although some studies on FZT metacercariae infections were conducted in fishes from Hantangang in Cheorwon-gun, Gangwon-do [ 15 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A team of Korean CDCP (Centers for Disease Control and Prevention) has performed the control project for zoonotic trematodiases in the adjacent residents of 5 major rivers, i.e., Nakdong-gang (gang means river), Seomjin-gang, Geum-gang, Yeongsangang and Han-gang, in Korea [6,7]. The team also participated in the surveys on the infection status of infective stage (metacercariae: infection sources) of ZT in fishes from water systems of major rivers in Korea [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%